'Machiavellian Russia' in the Crimean conflict: Clarification of strategic narratives analysis method. (April 2022) - Gackowski, Tomasz; Brylska, Karolina
The article concerns the strategic narratives concept as a tool of soft power and proposes methods and techniques of analysing strategic narratives. We argue that the best approach should apply a methodological triangulation which combines different methods and techniques while simultaneously addressing gaps in the implementation of theoretical perspectives. We present a theoretical concept of analysis and validate it using the example of a case study of the Crimea conflict in 2014 and 2015. Relying on the following three sources of original data: content analysis of media coverage (press comments over 8 weeks of 2014 and 2015), a cross-sectional survey (Computer Assisted Telephone Interviewing), and survey and focus group interviewing on the reception of Internet memes; we show that a strategic narrative works both in the media and in the opinions of media recipients. Investigating the 'Machiavellian Russia' strategic narrative, we show that mass-media interpretation of present events seems to depend on historical context and comparisons, which create a specific bubble around recipients of media messages.